Skin Mucus as a Relevant Low-Invasive Biological Matrix for the Measurement of an Acute Stress Response in Rainbow Trout (Oncorhynchus Mykiss) - Reyes-Lopez, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Skin mucus is a non-lethal and low-invasive matrix appropriate to assess fish welfare as it contributes to their defence against external aggressions and reflects changes in fish health status. However, more information on the response of this matrix to specific stressors is needed. In this study, rainbow trout (Oncorhynchus mykiss) specimens were subjected to an acute stress by air exposure and sampled after 1, 6, and 24 h post-stress. Blood and skin mucus were collected, and a battery of biochemical biomarkers were measured in both matrices. Cortisol and glucose values showed the expected classical stress response in plasma, increasing after the acute stress. The same pattern was observed in skin mucus, corroborating previous data in fish, and allowing us to confirm that skin mucus can be a useful complementary matrix for stress assessment in fish. The results showed sensitivity to hypoxic stress in skin mucus for cortisol, glucose, alkaline phosphatase (ALP), aspartate transaminase (AST), alanine aminotransferase (ALT), creatinine kinase (CK), and calcium. From the 15 parameters evaluated, 12 did not show statistically significant changes between plasma and mucus; therefore, using skin mucus cannot replace the use of plasma. Finally, the principal component analysis in skin mucus revealed a complete separation between the two experimental groups, being ALP, AST, glucose, cortisol, and CK, the biomarkers that contributed the most to this separation. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: biomarkers; skin mucus; fish; acute stress; rainbow trout